2002
DOI: 10.1001/archpedi.156.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Ampicillin Use in Infant Fever

Abstract: The empirical use of ampicillin to cover febrile infants for L monocytogenes and enterococcal infections is most justifiable in the first month of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 103 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…We observed that overall resource utilization, antimicrobial use, and hospitalization rates varied across hospitals, but little variation was observed in revisit outcomes. Ampicillin has traditionally been administered to neonates suspected of having Listeria monocytogenes, an uncommon cause of bacteremia and meningitis in the febrile young infant, [34][35][36][37] especially beyond the first month of life, 38 and Enterococcus, similarly an uncommon cause of SBI. 34,37,38 Additionally, the prevalence of ampicillin resistance has been reported to be 36% to 53% in pathogens that cause SBI in the febrile young infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that overall resource utilization, antimicrobial use, and hospitalization rates varied across hospitals, but little variation was observed in revisit outcomes. Ampicillin has traditionally been administered to neonates suspected of having Listeria monocytogenes, an uncommon cause of bacteremia and meningitis in the febrile young infant, [34][35][36][37] especially beyond the first month of life, 38 and Enterococcus, similarly an uncommon cause of SBI. 34,37,38 Additionally, the prevalence of ampicillin resistance has been reported to be 36% to 53% in pathogens that cause SBI in the febrile young infant.…”
Section: Discussionmentioning
confidence: 99%
“…Ampicillin has traditionally been administered to neonates suspected of having Listeria monocytogenes, an uncommon cause of bacteremia and meningitis in the febrile young infant, [34][35][36][37] especially beyond the first month of life, 38 and Enterococcus, similarly an uncommon cause of SBI. 34,37,38 Additionally, the prevalence of ampicillin resistance has been reported to be 36% to 53% in pathogens that cause SBI in the febrile young infant. 34,39 Despite these findings, nearly two-thirds of hospitalized febrile infants in our study received ampicillin in combination with gentamicin or a third-generation cephalosporin, with significant interhospital variation.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the four innate host factors studied exhibited unique spectrums of antimicrobial activity against the most common bacterial pathogens in neonatal infections, including E. coli, Enterococcus species, group B Streptococcus, H. influenzae, Klebsiella species, L. monocytogenes, P. aeruginosa, coagulase-negative Staphylococcus, and Staphylococcus aureus (35)(36)(37)(38)(39). These antimicrobial factors have complimentary activities, because each peptide has different bacterial spectrum and salt sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence to determine the optimal age at which ampicillin therapy is no longer needed as a part of empirical antibiotic regimens. [4] Data from developed countries suggest that empirical ampicillin therapy is no longer needed after 1 month of age, [17] and there are limited data in Africa to support this practice; however, we have no data regarding the prevalence of LM infection at our institution.…”
Section: Researchmentioning
confidence: 91%
“…This was thought to be due to low availability of common potential food contamination sources. [16] The addition of ampicillin to a thirdgeneration cephalosporin for suspected neonatal sepsis and meningitis in neonates and infants aged <90 days seems to be appropriate, as most studies [4,7] show that LM is rare after 30 days of age. The question remains whether the empirical addi tion of ampicillin to a third-generation cephalosporin cannot be further restricted.…”
Section: Researchmentioning
confidence: 99%